The secret to Southern charm [large type] - Harvey, Kristy Woodson (The peachtree bluff series, 2018)
"Leaving fans "practically [begging] for a sequel" (Bookpage), critically acclaimed author Kristy Woodson Harvey returns with the second novel in her beloved Peachtree Bluff series, featuring a trio of sisters and their mother who discover a truth that will change not only the way they see themselves, but also how they fit together as a family"--